Investigation of antimicrobial activity of aqueous extracts of Eclipta prostrate - Prabagar, S.; Nanthakumar, J.; Thuraisingam, S.; Prabagar, J. (Research gate, 2020)
Eclipta prostrata is a small herb distributed in tropical regions of the world. It is commonly known as false daisy. The plant is used in Ayurvedic medicine for skin infections and some non-communicable diseases. Aqueous extraction of plant material such as leaf and whole plant were investigated for anti-microbial activity without changing concentration. Results of study revealed that all extracts had inhibitory activity against E.coli with the clear zone of 1.3cm, which is similar to streptomycin control. Antifungal activity of leaf and whole plant extract of Eclipta prostrata against Aspergillus and Rhizopus showed the inhibitory growth ranged from 23.5 % to 33.30% whereas the leaf extract showed high inhibition than whole plant extract. The findings exhibit that leaf and whole plant aqueous extracts have narrow spectrum activity and there is a possibility in treatment of infectious diseases
Keywords: Eclipta prostrata; Leaf and whole plant extracts; Antimicrobial activity